MANFAAT E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI: PENDORONG MINAT MAHASISWA AKUNTANSI UNTUK BERWIRAUSAHA - Shania Marcelina; Mitha Restuti (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
The development of technology in business makes it convenient for entrepreneurs to run their businesses but then creates tighter competition. Entrepreneurs who cannot compete will lose the opportunity to develop their business. It is necessary to get the advantage from technology growth information. This study aims to test the impact of e-commerce's benefits and accounting information systems on the entrepreneurship interest of accounting students. The sample of this research was 241 observations. This study used questionnaires to collect the data and analyze it with regression. This study documented that e-commerce's benefits and accounting information systems encourage entrepreneurship interest in accounting students. Based on the theory of the Technology Acceptance Model (TAM) can explain the perceived benefits and ease of use of technology and the relationship between the benefits of e-commerce and accounting information systems on accounting students' interest in entrepreneurship.